MANUSCRIPT PUBLICATION MONITORING SYSTEM - Yap, Dudley Wei Yang (Universiti Malaysia Sarawak (UNIMAS), 2019)
Publication is the process of making of a book or a journal available for general public. Publication consists of many steps and consume a lot of time before successfully publishing a book or a journal. Nowadays, most publication companies use online publication system to manage their works as it is simpler, easier and more convenient. As Universiti Malaysia Sarawak (UNIMAS) Publisher does not have a publication system of their own, they can only manage their publication manually. Therefore, the main purpose of this project is to develop and design a manuscript publication monitoring system to help reduce the workload of UNIMAS Publisher and shorten the time taken for the publication process.